Pengaruh Kualitas Pelayanan, Kepuasan, Trust, Brand Equity, Hospital Image dan Komitmen terhadap Loyalitas Pasien Umum - Sihombing, Yolanda Anastasia (Jurnal Ayurveda Medistra, 2021)
The competition of bussines in hospital nowdays has been entering an era of high competition. Where all the hospital are trying to compete in maintaining the costumer they had. These experiment is intend to analyze the impression of good service, satisfactory, trust, commitment, brand equity, hospital image toward the outpatient. The method of research that used is quantitative with the design of cross-sectional. The analyze method(SEM) with smart PLS 2.0 an SPSS 18. The result of hipotesis resting using Structural Equation Model SEM is the loyality of outpatient in RS kesdam Cijantung is affected by the quality of services (23.19%) satisfactory(18.27%) trust(11.08%) commitment (6.28%) brand equaty (15.58%) and hospital image (9.35%) this is a direct influences (83.86%) while the indirect influence is (0.87%). The result of this analyze model explained (71.95%) of vary data and able to review fenomena that used in research, in contrary (28.05%) is explained as difficult component in this experiment. In conclusion toward this research that the services quality is the most influence variable that effect patient loyality.